PREVALENCE OF CERCARIAE INFECTION AMONG FRESHWATER SNAILS AROUND IRRIGATION SCHEMES, IN THE BENUE RIVER VALLEY, ADAMAWA STATE, NIGERIA - DANIEL, JL; CHESSED, G; VANDI, P; AUGUSTINE, LM (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Schistosomiasis and fascioliasis are similar in their life cycles in which freshwater snails that act as intermediate host. The aim of the study was to assess the rate of cercaria shedding in snails collected around irrigation schemes in the Benue River Valley of Yola South, Adamawa State, Nigeria. Freshwater snails sampled were kept in the aquaria for 2-3 days to acclimatize and fed with aquatic vegetation. Each snail was placed in a beaker and exposed to morning sunlight. The beakers were observed for the presence of cercariae using hand lens and microscope in the Department of Zoology, Modibbo Adama University, Yola. The distribution of freshwater snail’s species, showed that a total of 1,620 snails were sampled with Njoboliyo having the highest number of snails with 373, followed by Lake Geriyo with 287, Dasin Hausa with 266, Rugange with 255, Dasin Bwattiye with 235, while Boronji had the least with 204 freshwater snails. Overall-in the wet season: - Bulinus globosus being the most abundant snail, with a total of 287 (28.47%) snails, and the least B. truncatus with 228 (22.62%). The distribution of cercaria in the wet season; the highest was in B. globosus with 23 (32.39%), the least was in B. truncatus with 14 (19.72%). A total of 612 freshwater snails were collected in the dry season. B. globosus was most abundant snail with 173 (28.27%) snails, the least being B. reticulatus 144 (23.53%). The cercaria shedding showed that the highest was in B. reticulatus with 38 (33.63%), the least was in B. truncatus with 22 (19.47%). All species shade cercaria in all the communities